Association of the lymphocyte-to–C-reactive protein ratio with long-term mortality in hospitalized older adults with severe dysphagia - Zhong, Xuejin; Huang, Dongjie; Chen, Yuling; Chen, Zeru; Chen, Xiaomi; Zhou, Shuyue; Lu, Yutong; Huang, Nuoyan; Wu, Xiaoling; Chen, Haiwei; Chen, Mingdi (Frontiers in Nutrition, 2026)
BackgroundDysphagia is highly prevalent among older adults and is strongly associated with malnutrition, chronic inflammation, and multiple comorbidities, all of which contribute to increased mortality. The lymphocyte-to–C-reactive protein ratio (LCR) has recently gained attention as an immunonutritional biomarker, yet its prognostic relevance in elderly individuals with dysphagia remains unclear. This study examined whether LCR is associated with long-term all-cause mortality in this population.MethodsThis study used a retrospective cohort design involving elderly individuals with dysphagia who underwent either percutaneous endoscopic gastrostomy or total parenteral nutrition from 2014 to 2017. The LCR was converted to its natural logarithmic form and grouped according to its quartile distribution. Survival was analyzed through time-to-event methods, including Kaplan–Meier estimation and multivariable Cox regression. The shape of the association was explored using restricted cubic spline modeling, and several additional analyses were carried out to evaluate the stability of the findings.ResultsThe analytic sample comprised 248 older adults, whose mean age was 83.0 years. Survival differed significantly across Ln-LCR quartiles, and higher Ln-LCR values were consistently associated with lower mortality risk. In adjusted Cox models, each one-unit increase in Ln-LCR was associated with a lower hazard of all-cause mortality. Quartile analyses demonstrated a clear graded pattern, and spline models indicated a predominantly linear inverse association, with substantially elevated risk at Ln-LCR values below −1.99. Sensitivity analyses supported the stability of these findings.ConclusionLn-LCR was independently associated with long-term all-cause mortality risk in this cohort and may serve as a convenient prognostic marker for clinical risk stratification. Lower Ln-LCR values may help identify individuals at particularly high risk.